Evaluation of Acute Insecticide Poisoning Cases with Postmortem Examination in Bursa - Türkmen, Nursel; Fedakar, Recep; Çetin, Volkan; Durak, Dilek (The Bulletin of Legal Medicine, 2002)
Background: Poisoning with insecticides is one of the important issues among intoxications in our country. In this study, we tried to profile insecticide poisoning cases in Bursa region. Material and methods: 3575 forensic cases, performed autopsy at Council of Forensic Medicine Bursa Morgue Department between the years 1996 and 2002, were reviewed. 365 cases with a prediagnosis of poisoning were included in the study. Results: 91 (24.93%) of total 365 poisoning cases was determined as insecticide poisoning. 65 (71.43%) of cases was male, 26 (28.57%) was female 28 (19.78%) of cases was in the age group of 20-49 and the most common origin was suicide. Organic phosphorous compounds were leading agent among the responsible compounds. Conclusion: The data collected is compared with similar studies carried out in different regions, results are discussed and suggestions are presented. Keywords: Insecticide, poisoning, death, autopsy